Pegcetacoplan for the treatment of geographic atrophy due to age-related macular degeneration: a plain language summary of OAKS and DERBY clinical studies - Heier, Jeffrey S; Lad, Eleonora M; Holz, Frank G; Rosenfeld, Philip J; Guymer, Robyn H; Boyer, David; Grossi, Federico; Baumal, Caroline R; Korobelnik, Jean-Francois; Slakter, Jason S; Waheed, Nadia K; Metlapally, Ravi; et al. (Immunotherapy, 2025)
What is this summary about?This is a summary of the results of 2 clinical studies , called OAKS and DERBY, that tested a medicine called pegcetacoplan. Pegcetacoplan is the first United States Food and Drug Administration (US FDA) approved treatment for geographic atrophy, commonly referred to as GA, a common eye disease in older people. Geographic atrophy is a form of late age-related macular degeneration, or AMD, that usually starts after age 50. The US FDA approved pegcetacoplan based on the results from these 2 clinical studies. Pegcetacoplan is covered by Medicare and most insurance companies in the United States.What are the key takeaways?The results of the OAKS and DERBY clinical studies show that treatment with pegcetacoplan led to slower growth of GA lesions in the retina. The retina is the light-sensitive tissue at the back of the eye. In other words, it slowed the growth of the areas where cells were dying. When compared to a sham procedure, pegcetacoplan injection slowed the growth of lesions by 19% to 22% (when given every 4 weeks) and 16% to 18% (when given every 8 weeks) in OAKS and DERBY, respectively.After 2 years of treatment, there were no differences in the average vision function between participants treated with pegcetacoplan and participants who received a sham procedure.The most common eye-related health issues reported were like those reported with all types of intravitreal injections and most were temporary.What were the main conclusions reported by the researchers?Based on the results of these 2 large clinical studies, pegcetacoplan slows GA disease progression with an incidence of eye-related health issues similar to other drugs given by intravitreal injection.[Box: see text].